1971
DOI: 10.1530/jrf.0.0240247
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of the Motility of Rat Epididymal Spermatozoa in the Presence of Male Accessory Secretions

Abstract: The maintenance of motility and the survival of rat epididymal spermatozoa kept at 37\s=deg\C have been investigated. While progressive motility of long duration was observed when the epididymal spermatozoa of the hamster, guinea-pig and rabbit were suspended in balanced salt solutions, rat epididymal spermatozoa became immotile within 1 to 2 hr. The factor missing from the salt solutions which can maintain the motility of rat spermatozoa was shown to be present in the secretion from the seminal vesicles, epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…Morita & Chang (1971) also showed that the secretions of the coagulating glands and those of the seminal vesicles acted beneficially together to maintain the motility of rat epididymal spermatozoa.…”
Section: Introductionmentioning
confidence: 91%
“…Morita & Chang (1971) also showed that the secretions of the coagulating glands and those of the seminal vesicles acted beneficially together to maintain the motility of rat epididymal spermatozoa.…”
Section: Introductionmentioning
confidence: 91%
“…Finally, during ejaculation these cells are largely diluted with reproductive fluids derived from various accessory sex organs before being ejaculated into the female reproductive system. Although earlier workers have reported the occurrence multiple undefined sperm motility regulating protein factors in the male reproductive fluids and blood serum (Yanagimachi, 1970;Morita and Chang, 1971;Morton and Chang, 1973;Bavister, 1975;Gaur and Talwar, 1975;Morton et al, 1979;Sheth et al, 1981;Mandal et al, 1989;Majumder and Mandal, 1992;Majumder et al, 2001a), this study reports for the first time purification of a motilitypromoting protein (FMSF-I) to apparent homogeneity from a biological fluid (buffalo serum: the richest source of the factor), and some of its physical and biochemical characteristics. FMSF-I: the major motility promoter of blood serum is a heat-stable 66 KDa glycoprotein.…”
Section: Discussionmentioning
confidence: 78%
“…As reviewed earlier (Mandal et al, 1989;Majumder and Mandal, 1992;Majumder et al, 2001), there are several reports on the occurrence various types of sperm motility regulating protein factors in male reproductive fluids and blood serum. A motility maintenance factor has been demonstrated in rat seminal vesicle (Morita and Chang, 1971), sperm survival factor in hamster EP (Morton and Chang, 1973). Motility promoting factors have also been reported in human serum (Yanagimachi, 1970;Morton and Chang, 1973;Bavister, 1975;Morton et al, 1979), human seminal plasma (Gaur and Talwar, 1975), and human epididymal homogenate (Sheth et al, 1981).…”
mentioning
confidence: 92%
“…Over the years, researchers have reported on various types of sperm motility regulating protein factors in blood serum and reproductive fluids of both human and other species (Morita andChang 1971, 1973;Yanagimachi 1970;Bavister 1975;Morton et al 1979, Saha et al 2013. However, studies of these motility modulating proteins to identify their receptors on the maturing male gamete cell surface are not well reported, chiefly due to a lack of availability of such purified molecules.…”
Section: Introductionmentioning
confidence: 99%